Student Management to Strengthen Character Education in Elementary Madrasahs in the Digital Era: Manajemen kesiswaan untuk Memperkuat Pendidikan Karakter di Madrasah Ibtidaiyah pada Era Digital - Fadhilah; Ari Susetiyo; Asrofi; Moh. Nur Salim (Mapendis: Jurnal Manajemen Pendidikan Islam, 2024)
Character education in Madrasah Ibtidaiyah faces significant challenges in the digital era, particularly within the context of educational management. This study aims to identify and analyze both internal and external challenges and propose managerial strategies for strengthening character education amidst rapid technological advances. Utilizing a library research method, data was collected from various academic sources, including books, journals, and reports. The findings indicate that internal challenges include teachers' limited digital literacy, outdated curricula, weak infrastructure, and lack of visionary leadership. Externally, students' excessive exposure to digital entertainment, social media influences, and low digital literacy hinder the internalization of moral values. To address these challenges, the study suggests integrating digital literacy into character education through the Technological Pedagogical Content Knowledge (TPACK) framework, adopting blended learning, and fostering collaboration between schools and parents. Strengthening these strategies is expected to enhance Madrasah Ibtidaiyah’s ability to cultivate morally grounded, technology-wise students, adapting effectively to the dynamics of the digital era.